Importance of ultrasound measurement of the liver and spleen size in the diagnosis of comorbidity with malaria and COVID-19 - Krstić, Dušan; Krstić, Boban; Djokić, Milica; Rančić, Nemanja (Vojnosanitetski pregled, 2025)
Background/Aim. With the outbreak of the coronavirus disease 2019 (COVID-19) pandemic, patients who had malaria and COVID-19 simultaneously were also noticed. Hepatosplenomegaly is characteristic and almost always present in patients with malaria (without associated COVID-19). A significant increase in the size of the liver and spleen clearly indicates the possible development of severe malaria. The aim of this study was to determine the effect of COVID-19 on liver and spleen size in patients with malaria. Methods. This study was conducted while the authors were working in the Serbian Military Hospital of the United Nations Multidimensional Integrated Stabilization Mission (MINUSCA-UN) in Bangui, Central African Republic. Data from 1,710 patients who underwent ultrasound examination of the abdomen, where the diameters of the liver and spleen were monitored, were analyzed. The total number of examined patients was divided into four groups: group with 816 control patients without malaria (C group), 480 with active malaria (M+), 353 patients who had malaria in the past 2–6 months (Mpast), and 61 patients with active malaria and active COVID-19 (M+Cov+). Results. The liver size was significantly greater in the M+, Mpast, and M+Cov+ groups of respondents compared with the C group. Statistically significant spleen enlargement was observed only in the M+ group but not in the M+Cov+ group compared to the C group. Conclusion. There is no enlargement of the spleen in patients with a coinfection with the severe acute respiratory syndrome coronavirus 2 and Plasmodium malariae. Therefore, in the presence of clear splenomegaly, we can indicate, with a high probability, the absence of COVID-19 while waiting for the results of the polymerase chain reaction test, even in the first hours of hospitalization.